L’articulation entre enjeux environnementaux et aménités paysagères dans les politiques publiques des vallées du nord-ouest de la France - Marie-Anne Germaine; Aziz Ballouche (Projets de Paysage)
Valleys are subjected to significant environmental issues (flood, biodiversity) which are now in centre of planning questions. In this context, the aim of this paper is to measure the place public policies dedicate to landscape dimension in the regards on environmental ones. In particular, the consequences of environmental policies on visible forms of landscape are observed. The study is conducted from the example of the Orne valley which presents an original gorge valley landscape in Normandy. The part of Orne valley named Suisse Normande is a local famous tourist and leisure area. Planning policies analysis shows the predominance of environmental policies to landscapes ones. More generally, it reveals difficulties of the articulation of ecologic issues and amenities development.